2021
DOI: 10.1108/qae-07-2021-0114
|View full text |Cite
|
Sign up to set email alerts
|

Isomorphism and organizational performance: evidence from quality management in higher education

Abstract: Purpose Quality management has become an integral part of management reforms in public sector organizations. Drawing on a new institutionalist perspective, this study aims to investigate the relation of management reforms and organizational performance in the context of higher education. Design/methodology/approach The authors analyse the interaction between isomorphic conformity in quality management adoption, organizational learning and quality improvement and, in so doing, address the central theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…In the fourth and current paradigm, concepts of quality management attracted interest from sectors and areas in which competition is not direct but self-improvement is sought, such as education, public administration, and health care. Ansmann and Seyfried [28] indicate that quality management was an integral factor driving management reforms in public sector organizations over the past few decades, whereas Lunenburg [29] examines the implementation of TQM in schools. The latter approach is maintained by Díaz and Martínez-Mediano [30], who elaborate on the application of quality management systems in schools in Spain following effective implementation at the higher education level.…”
Section: Education and Tqmmentioning
confidence: 99%
“…In the fourth and current paradigm, concepts of quality management attracted interest from sectors and areas in which competition is not direct but self-improvement is sought, such as education, public administration, and health care. Ansmann and Seyfried [28] indicate that quality management was an integral factor driving management reforms in public sector organizations over the past few decades, whereas Lunenburg [29] examines the implementation of TQM in schools. The latter approach is maintained by Díaz and Martínez-Mediano [30], who elaborate on the application of quality management systems in schools in Spain following effective implementation at the higher education level.…”
Section: Education and Tqmmentioning
confidence: 99%
“…The results of this study not only assist Private Higher Learning Institutions (PHLI), but other fields of industry in identifying and modifying their priorities in business management to increase their possibility of becoming more sustainable and survivable. Prior studies indicated that management reforms has a positive impact toward organizational performance (Ansmann & Seyfried, 2022). There have been a number of industries that are hard pressed with the pandemic and unrecoverable, such as the tourism and airline industries (Go¨ssling et al, 2021).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Popular institutional theory is applied to provide a complete and broad perspective in the environment of public organizations (Ansmann & Seyfried, 2022;van Helden, 2005), in line with the NPM's idea to explain the background of public sector institutional reform (Alsharari, 2020;Rana, Ahmed, Narayan, & Zheng, 2021). The primary view of organizations is in the social environment, and the institutionalization process reflects the cultural rules and beliefs operating in the social environment (Scott, 2014); in meeting social expectations, organizations gain legitimacy, which is considered a significant factor for organizational survival (Meyer & Rowan, 1977).…”
Section: Literature Review Coercive Isomorphism and External Pressurementioning
confidence: 99%
“…Coercive isomorphism can lead to formal compliance but not actual change (Meyer & Rowan, 1977). Thus, it suggests that the lack of institutionalization is an implementation problem (Ansmann & Seyfried, 2022;Schilke, 2018).…”
Section: Hypothesis Development the Effect Of External Pressure On Th...mentioning
confidence: 99%
See 1 more Smart Citation